Solid Waste Management in Ludhiana City of Punjab (International Journal of Innovative Research in Engineering & Management, 2023)
Generation of solid waste at a very large scale has been a key issue in various countries of the world. Managing the municipal solid waste is a daunting and uphill task in various cities all over the world. Inadequate management of solid waste in India poses serious consequences to environment as well as to human health. For municipal authorities of various Indian cities, solid waste management is a complex challenge to tackle due to increasing pressure of population and different development perspectives. This uphill task of managing solid waste has influenced the Ludhiana city of Punjab. To investigate the current scenario and to carry out the implementation analysis of solid waste management in the city, the present study was  undertaken. This study investigates the situation of waste management of the city and concentrates on identifying the causes of rising challenge from the perspective of various stakeholders involved in the waste management of the city. Despite implementation of various solid  waste management programs by the municipal corporation Ludhiana, most of these have been unsuccessful. This study focuses on analysing the factors  that are responsible for hindering successful policy implementation of solid waste management in the city. For research purposes, a mixed methodology of quantitative and qualitative analysis was adopted. This research found out various financial, human resources, political and logistical constraints affecting the successful implementation of solid waste management program  in the city. At the implementation stage of solid waste management administrative constraints such as lack of modern technology and equipment’s,  insufficient of land for dumping and disposal, lack of integrated solid waste management program play a great role in being hindrances to the successful implementation. Based on the implementation analysis, the study proposes various policy recommendations to work out the challenges faced in successful  implementation of solid waste management in the city.
Keywords: Solid Waste; Environment; Human Health; Challenge